2010
DOI: 10.1111/j.1472-4642.2010.00696.x
|View full text |Cite
|
Sign up to set email alerts
|

Linking environmental conditions and ship movements to estimate invasive species transport across the global shipping network

Abstract: Aim  Some nations, and the International Maritime Organization, are moving towards requirements for managing ballast water to reduce the number of alien species transported and released. These and other measures will be most efficient when targeted at ships posing the greatest risks. Here, we analyse world‐wide ship movements and port environmental conditions to explore how these risk components differ across arriving ships. Location  Global, with a case study of the Laurentian Great Lakes. Methods  We gathere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
227
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(231 citation statements)
references
References 35 publications
(46 reference statements)
3
227
0
1
Order By: Relevance
“…The amount of exchanged commodities and the intensity of global traffic have therefore been found to be a good predictor to model the global spread of alien species (10)(11)(12). In most cases, predictions of alien species introductions are difficult to assess as model results could not be validated (i.e., quantitatively assessed using observed data) thoroughly due to the paucity of high-quality distributional data of alien species.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The amount of exchanged commodities and the intensity of global traffic have therefore been found to be a good predictor to model the global spread of alien species (10)(11)(12). In most cases, predictions of alien species introductions are difficult to assess as model results could not be validated (i.e., quantitatively assessed using observed data) thoroughly due to the paucity of high-quality distributional data of alien species.…”
mentioning
confidence: 99%
“…Without any model validation, however, it is nearly impossible to assess the quality and the reliability of model predictions, which hampers the application of models for the management of alien species. In recent years, appropriate highquality data have been made accessible by various online databases, but testing model predictions with these data has still been lacking.Model frameworks to predict the likelihood of new invasions have already been developed (10,11,13). However, these were not able to predict the identity of new invaders, but only the likelihood that any new species arrives from a certain source region on Earth.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Invasion risks associated with shipping have been examined recently for specific recipient systems (6,12) and for a small group of species (13). Studies have identified high-risk invasion routes and invasion hotspots (14,15), but no previous study has tested a modeling approach that predicts both the identity and likelihood of establishment of alien species on a global scale.…”
Section: Ships As Global Dispersers Of Aquatic Organismsmentioning
confidence: 99%
“…However, invasive species do alter marine ecosystems to a large extent and have been shown to introduce diseases, displace native species, alter food-web dynamics, and drive local declines and shifts in habitat type (Briggs, 2010;Pyšek and Richardson, 2010;Crain et al, 2009). Keller et al (2011) coupled environmental niche-and vector-based models to assess "invasion risk" of global ports due to global shipping traffic. They used global databases of ship traffic and port environmental conditions to assess the chance that individual arriving ships will contain organisms capable of surviving in the recipient port.…”
Section: Cause-effectmentioning
confidence: 99%